The anthropologist's last bow: Ontology and mysticism in pursuit of the sacred. (September 2019) - Baldacchino, Jean-Paul
The religious beliefs and experiences of others have long been grist to the anthropological mill. In much anthropological scholarship however there is a resolute silence on the anthropologists' own relationship to the domain of the 'spirit'. Recent scholarship in the anthropology of religion has been highly critical of the Christian underpinnings of much of what is ostensibly secular anthropology (as in the works of Evans-Pritchard, Mary Douglas and Victor Turner among others). The commitment to a religious belief, if not simply a religious upbringing, was seen to be a 'polluting' influence to the proper study of the religion of others in their own terms. In turn scholars adopting a genealogical approach have shown how the very discipline of a secular anthropology of religion is itself the product of a highly Christian intellectual legacy. In his later years, anthropologist, friend and mentor Joel Kahn turned his attention precisely to the study of the pursuit of the sacred in a secular age. Starting from what he describes as his own 'ontological crisis' as a secular American Jew Kahn looks to the Western encounter with Asian religion to set out the domain of what he calls 'gnostic scholarship' that looks to the religion of others not as a cultural artefact but as, ultimately, a source of radical subjective displacement. In the spirit and memory of Joel Kahn this paper discusses the anthropological encounter with the sacred not as an object of knowledge about 'cultures' but as a source of gnosis. Expanding on the implications of Joel's work for an anthropology of religion this work draws upon the author's fieldwork among Catholic devotees of Padre Pio to propose a form of embodied surrender as a pre-requisite for an intersubjective engagement with the ontologically other worlds of our informants.